Treatment of indolent cutaneous B-cell lymphoma with intralesional or intravenous Rituximab - Menzer, Christian; Rendon, Adriana; Hassel, Jessica C. (Cancers, 2022)
Indolent cutaneous B-cell lymphomas (CBCL) are a rare disease for which the therapeutic recommendations are based on clinical reports. Recommendations for solitary lesions include surgery or irradiation. However, the high relapse rates may require less invasive repeatable therapy. This study seeks to retrospectively assess the efficacy of intralesional rituximab (ILR) for indolent CBCL when compared with intravenous rituximab (IVR). Patients treated for indolent CBCL with ILR or IVR at the Division of DermatoOncology of the University Hospital Heidelberg were eligible for this study. Characteristics of lymphoma, treatment response, and adverse events were assessed. Twenty-one patients, 67% male at a median age of 52 (range 17-80), were included. Nineteen (90%) had only localized lymphoma (stage T1 and T2). Complete response was achieved in 92% (11/12) of ILR after a median of one cycle (three injections) and 78% (7/8) of IVR patients after a median of six cycles. Half of ILR patients and 78% of IVR patients showed relapse after a median of 15 and 23 months, respectively. Adverse reactions were usually mild and were limited to the first injection of ILR. One patient with IVR contracted a pulmonary infection. ILR may be an alternative to the intravenous administration of rituximab for localized indolent CBCL.
Gesehen am 04.01.2023